Gastrointestinal hormone mRNA expression in human colonic adenocarcinomas, hepatic metastases and cell lines. Issue 3 (June 1996) - Monges, G; Biagini, P; Cantaloube, J F; De Micco, P; Parriaux, D; Seitz, J F; Delpero, J R; Hassoun, J
Abstract : Aims —(1) To investigate the expression of the four main hormones of the digestive tract by performing reverse transcription polymerase chain reaction (RT-PCR) on a series of samples, comprising tumoral and healthy colonic tissues, hepatic metastases and colonic cell line samples; and (2) to study the patterns of labelling obtained with serological and morphological markers. Methods —After extraction and reverse transcription, gastrin, somatostatin, cholecystokinin (CCK) and transforming growth factor α (TGFα) mRNAs were detected by PCR and nested PCR using specific primers. The corresponding proteins were detected by immunohistochemistry. Results —The cell lines expressed all four mRNAs. Gastrin mRNA was present in most tumoral and metastatic samples, while the somatostatin transcript was detected in all samples and was frequently overexpressed in the normal colon. TGFα mRNA was expressed systematically in tumours of the right and transverse colon, but not in those located in the left colon; the expression of CCK mRNA was systematically absent in the left colon. Conclusions —The data presented here shed some light on the transcriptional events involved in the production of the various hormones present in the gastrointestinal tract, in both healthy and tumoral tissues. The various mRNAs expressed in cell lines are therefore not systematically expressed in the human pathology.